Long-term effect of integrated nutrient management on yield and nutrients uptake by rice (Oryza sativa) in acid soil - PATRA, ABHIK; SHARMA, V K; PURAKAYASTHA, T J; BARMAN, MANDIRA; KUMAR, SARVENDRA; CHAKRABORTY, D; CHOBHE, KAPIL A; NATH, D J (The Indian Journal of Agricultural Sciences, 2018)
Long-term field experiment on rice commenced in kharif 2006 at Instructional-cum-Research farm of the Assam Agricultural University, Jorhat with integrated nutrient management practices for assessing its impact on yield and nutrient uptake by rice in acid soil. The treatments consisted of T1, absolute control; T2,100% recommended doses (RD) of inorganic NPK; T3, 50% RD of inorganic NP + 100% K + biofertilizers; T4, 50% RD of inorganic NP + 100% K + enriched compost @ 1 tonne/ha; and T5, 25% RD of inorganic NP + 100% K + enriched compost @ 2 tonnes/ha. Results revealed that after 10 years of experiment, grain yield of rice (4.43 t/ha) increased significantly with 100% NPK by 10.8 and 78.6 % over 50% NP+100% K+ bio-fertilizers and control, respectively and it was at par with 25% NP + 100% K+ enriched compost @ 2 t/ha (4.38 t/ha). Whereas, the maximum straw yield (5.18 t/ha) was recorded with 25% NP + 100% K+ enriched compost @ 2 t/ha which was higher significantly over 50% NP and 100% K+ bio-fertilizers (4.63 t/ha) and control (3.08 t/ha), respectively and total nutrient uptake, i.e. N, P, K, Zn, Cu and Ni by rice was significantly higher in 25% RD of inorganic NP + 100% K + enriched compost @ 2 tonnes/ha treatment as compared to recommended dose of fertilizer (100% NPK) in acid soil but total aluminium uptake by rice significantly decreased with the application of reduced doses of NP along with higher dose of enriched compost (2 t/ha). Therefore, aluminium toxicity level in rice plant under acidic condition could be reduced through enriched compost application.